Histone variant macroH2A: from chromatin deposition to molecular function. Issue 1 (2nd April 2019) - Sun, Zhen; Bernstein, Emily
Abstract : The eukaryotic genome is regulated in the context of chromatin. Specialized histones, known as histone variants, incorporate into chromatin to replace their canonical counterparts and represent an important layer of regulation to diversify the structural characteristics and functional outputs of chromatin. MacroH2A is an unusual histone variant with a bulky C-terminal non-histone domain that distinguishes it from all other histones. It is a critical player in stabilizing differentiated cell identity by posing as a barrier to somatic cell reprogramming toward pluripotency and acts as a tumor suppressor in a wide range of cancers. MacroH2A histones are generally regarded as repressive variants that are enriched at the inactive X chromosome (Xi) and broad domains across autosomal chromatin. Recent studies have shed light on to how macroH2A influences transcriptional outputs within distinct genomic contexts and revealed new intriguing molecular functions of macroH2A variants beyond transcriptional regulation. Furthermore, the mechanisms of its mysterious chromatin deposition are beginning to be unraveled, facilitating our understanding of its complex regulation of genome function.